2021
DOI: 10.1159/000511940
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CA19-9 and Blood Free-Circulating Methylated <b><i>RUNX3</i></b> May Be Useful to Diagnose Stage I Pancreatic Cancer

Abstract: <b><i>Background:</i></b> Although serum carbohydrate antigen 19-9 (CA19-9) is widely used as a useful biomarker of pancreatic cancer for monitoring the response to therapy, it is not recommended for screening of early pancreatic cancer because of its limited sensitivity for small tumors. Thus, it is critical to discover novel serum biomarkers to complement CA19-9 in order to improve sensitivity. Although methylated runt-related transcription factor 3 (<i>RUNX3</i>) is a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The use of serum tumor markers in the diagnosis of pancreatic cancer is also the focus of clinical research. Fujimoto et al [ 12 ] combined the serum marker CA19-9 and methylated short stature-related transcription factor 3 (RUNX 3) in early pancreatic cancer screening and found that the sensitivity and the specificity of the two combined detection of pancreatic cancer were 85.5% and 93.5%, respectively, showing good diagnostic effect. Dong et al [ 13 ] analyzed the diagnostic value of CA19-9, CA 242, and serum peripherin (POSTN) for pancreatic cancer and finally found that CA19-9 and CA 242 combined with POSTN detection was a potential serum marker for the diagnosis of early pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The use of serum tumor markers in the diagnosis of pancreatic cancer is also the focus of clinical research. Fujimoto et al [ 12 ] combined the serum marker CA19-9 and methylated short stature-related transcription factor 3 (RUNX 3) in early pancreatic cancer screening and found that the sensitivity and the specificity of the two combined detection of pancreatic cancer were 85.5% and 93.5%, respectively, showing good diagnostic effect. Dong et al [ 13 ] analyzed the diagnostic value of CA19-9, CA 242, and serum peripherin (POSTN) for pancreatic cancer and finally found that CA19-9 and CA 242 combined with POSTN detection was a potential serum marker for the diagnosis of early pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, so far, the results from the validation study of the diagnostic gene panel developed by our group, which is based on hypermethylation of eight genes in combination with CA-19-9 shows a promising performance. This together with the other studies illustrating improved performance in combination with KRAS mutation [ 37 ] or CA-19-9 [ 36 ], indicate a panel of hypermethylated genes in combination with other diagnostic modalities might be needed to bolster the diagnostic power, which seems reasonable keeping in mind the molecular heterogenicity of PDAC.…”
Section: Cell-free Dna Methylation As Diagnostic Biomarkers For Pdacmentioning
confidence: 71%
“…RUNX3 methylation had a sensitivity of 50.9% for PDAC, with a 93.5% specificity using the total control group. By combining RUNX3 methylation and CA-19-9 the sensitivity increased substantial (85.5%) [ 36 ]. Furthermore, Keiko Shinjo and coworkers [ 37 ] examined methylation status of five genes ( ADAMTS1 , HOXA1 , PCDH10 , SEMA5A and SPSB4 in serum from patients with PDAC ( n = 47) and healthy controls ( n = 14).…”
Section: Cell-free Dna Methylation As Diagnostic Biomarkers For Pdacmentioning
confidence: 99%
“…The majority of patients are unresectable (75–80%) [ 20 , 21 , 22 , 23 ] and have a low 5-year overall survival rate [ 24 , 25 , 26 ]. CA19-9 is not recommended for screening early pancreatic cancer because of its limited sensitivity [ 27 , 28 , 29 ], especially in small tumors [ 30 ]. Hence, detection for early-stage PDAC and the evaluation of PDAC prognosis remain difficult problems.…”
Section: Discussionmentioning
confidence: 99%